The impact of public guarantees on bank risk taking: evidence from a natural experiment - Reint E. Gropp; Christian Gruendl; Andre Guettler (European Central Bank (ECB), 2010)
In 2001, government guarantees for savings banks in Germany were removed following a law suit. We use this natural experiment to examine the effect of government guarantees on bank risk taking, using a large data set of matched bank/borrower information. The results suggest that banks whose government guarantee was removed reduced credit risk by cutting off the riskiest borrowers from credit. At the same time, the banks also increased interest rates on their remaining borrowers. The effects are economically large: the Z-Score of average borrowers increased by 7.5% and the average loan size declined by 17.2%. Remaining borrowers paid 46 basis points higher interest rates, despite their higher quality. Using a difference-in-differences approach we show that the effect is larger for banks that ex ante benefited more from the guarantee and that none of these effects are present in a control group of German banks to whom the guarantee was not applicable. Furthermore, savings banks adjusted their liabilities away from risk-sensitive debt instruments after the removal of the guarantee, while we do not observe this for the control group. We also document in an event study that yield spreads of savings banks' bonds increased significantly right after the announcement of the decision to remove guarantees, while the yield spread of a sample of bonds issued by the control group remained unchanged. The results suggest that public guarantees may be associated with substantial moral hazard effects.
Keywords: G21; G28; G32; 330; banking; Credit risk; market discipline; Moral Hazard; public guarantees; Bankenliquidität; Subvention; Kreditrisiko; Moral Hazard; Bankenregulierung; Deutschland